Letter to Jane Tolmach from Joseph R. Cerrell - Joseph R. Cerrell:::::: (1961)
A letter to Jane Tolmach from Joseph R. Cerrell of the Democratic National Committee. The letter informs Jane that he has recieved a copy of the letter that Governor Brown sent her and to reach out if further assistance is needed.